Le Canada, ou Nouvelle France, etc. - Sanson, Nicolas, 1600-1667.;Somer, Jean. (North Carolina Department of Cultural Resources, 1656)
Shows "New France" from the Hudson Bay to the north extending to modern-day South Carolina to the South; includes the Great Lakes, St. Lawrence River, and Appalachian Mountains. Also includes Native American and European settlements. There are several blank areas on the map demonstrating the limits of geographical knowledge during this period. This is a 1656 map of Canada first published in Paris as a loose map. This map was formerly classified as 33 MAP-0-13